2021
DOI: 10.3389/fmicb.2021.685343
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Effects of Acquisition of the Phage-Encoded ssa Superantigen Gene in Invasive Group A Streptococcus

Abstract: The acquisition of the phage-encoded superantigen ssa by scarlet fever-associated group A Streptococcus (Streptococcus pyogenes, GAS) is found in North Asia. Nonetheless, the impact of acquiring ssa by GAS in invasive infections is unclear. This study initially analyzed the prevalence of ssa+ GAS among isolates from sterile tissues and blood. Among 220 isolates in northern Taiwan, the prevalence of ssa+ isolates increased from 1.5% in 2008–2010 to 40% in 2017–2019. Spontaneous mutations in covR/covS, which res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Our previous study identified, by Phostag Western blotting ( Fig. 1B ), 29 CovS-inactivated clinical isolates ( 31 ). In this study, we found that only nine isolates (31%) exhibited a distinguishable encapsulated colony morphology ( Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Our previous study identified, by Phostag Western blotting ( Fig. 1B ), 29 CovS-inactivated clinical isolates ( 31 ). In this study, we found that only nine isolates (31%) exhibited a distinguishable encapsulated colony morphology ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Strain AP3 is a mouse-passaged isolate of A20 which has a frameshift deletion in the covS gene ( 33 ) and was designed as the covS mutant in this study. The rocA mutant, RocA-truncated mutant, hasA mutants, and CovR/CovS-inactivated clinical isolates have been described previously ( 26 , 31 , 33 ). GAS strains were cultured on Trypticase soy agar containing 5% sheep blood or in tryptic soy broth (Becton, Dickinson and Co., Sparks, MD, USA) supplemented with 0.5% yeast extract (TSBY).…”
Section: Methodsmentioning
confidence: 99%
“…This new clone can be differentiated from M1global by 27 lineage-defining single-nucleotide polymorphisms (SNP) and is characterized by increased SpeA production (11,17), resulting from a SNP in the transfermessenger RNA gene ssrA (15). Numerous countries, including the United States, Canada, the Netherlands, Australia, and Taiwan, have reported on the presence and expansion of the M1UK lineage among iGAS patients, confirming global dissemination and further evolution of this new variant (15,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 98%